Early amiodarone or lidocaine administration during in-hospital cardiac arrest caused by shockable rhythms - Rafael C. Paganoni; Jack C. Pluenneke; Adham M. Mohamed; Charles H. Hayes, III; Carole E. Freiberger-O’Keefe; Paul S. Chan (Resuscitation Plus)
Introduction: Published data investigating a time-dependent effect of initiation of antiarrhythmic therapy for shockable in-hospital cardiac arrest (IHCA) is lacking. We aimed to evaluate the association between time of intravenous amiodarone or lidocaine administration and return of spontaneous circulation (ROSC) in patients with IHCA caused by ventricular fibrillation (VF) or pulseless ventricular tachycardia (pVT). Methods: This was a retrospective, multi-center, single health system, observational cohort study of patients with an IHCA caused by VF/pVT and who received amiodarone or lidocaine during 2014–2024. The primary outcome was ROSC, and the secondary outcome was survival to hospital discharge. A multivariable logistic regression model was constructed to evaluate the association between (1) time to drug administration and (2) drug administration prior to the second defibrillator shock on both survival outcomes. Results: A total of 88 patients with a shockable IHCA were identified. Longer time to amiodarone or lidocaine administration was associated with lower likelihood of ROSC (adjusted odds ratio [aOR] 0.91; 95% CI: 0.83–0.99, P = 0.04) but not with survival to discharge (aOR 0.99; CI 0.90–1.10P = 0.90). Administration of antiarrhythmic therapy prior to the second defibrillator shock was associated with higher likelihood of ROSC (aOR 6.48; CI 2.08–20.21, P = 0.001) and survival to discharge (aOR 2.82; CI 1.03–7.77, P = 0.04). Conclusion: Early administration of amiodarone or lidocaine, particularly prior to the second defibrillator shock, was associated with an increased odds of survival outcomes in IHCA with shockable rhythms.